2022
DOI: 10.1021/acs.jcim.2c00414
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Atomistic Mechanisms of Phosphorylation in Disrupting Liquid–Liquid Phase Separation and Aggregation of the FUS Low-Complexity Domain

Abstract: Fused in sarcoma (FUS), a nuclear RNA binding protein, can not only undergo liquid−liquid phase separation (LLPS) to form dynamic biomolecular condensates but also aggregate into solid amyloid fibrils which are associated with the pathology of amyotrophic lateral sclerosis and frontotemporal lobar degeneration diseases. Phosphorylation in the FUS lowcomplexity domain (FUS-LC) inhibits FUS LLPS and aggregation. However, it remains largely elusive what are the underlying atomistic mechanisms of this inhibitory e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 75 publications
2
23
0
Order By: Relevance
“…Lao et al . used AMBER99SB-ILDN (with TIP3P water model) to simulate a longer region of FUS including the R2-FUS-LC region 37 . Comparing with their contact maps, we observe similar contact patterns in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lao et al . used AMBER99SB-ILDN (with TIP3P water model) to simulate a longer region of FUS including the R2-FUS-LC region 37 . Comparing with their contact maps, we observe similar contact patterns in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Lao et al . suggested that the S54/S61 and Y55 in R2 region of FUS-LC-core (R2-FUS-LC region) are involved in the stability of the RAC 37 while Ding et al . showed that R2 is the most fibrilized repeat region 31 .…”
Section: Introductionmentioning
confidence: 99%
“…46−49 The reason for choosing AMBER99SB-ILDN used in our study is that this force field was in good agreement with the experimental NMR and CD measurements. 50,51 Lengths of chemical bonds within the protein and solvent were con-…”
Section: ■ Methodsmentioning
confidence: 99%
“…The secondary structure of the TDP-43 protofilament was analyzed using the dictionary of the secondary structure of proteins method . A hydrogen-bond is formed if (i) the distance between a donor atom (D) and an acceptor atom (A) is no larger than 3.5 Å and (ii) the angle of D–H···A is no less than 150°. ,− A salt bridge is considered to be formed between an NH 3 + group and a COO – group when the centroid distance between them is less than 4.0 Å. An atomic contact is defined when two aliphatic carbon atoms were within 5.4 Å or any other two heavy atoms were within 4.6 Å. ,, The PMF was calculated using the relation F = − RT ln P ( x , y ), where P ( x , y ) is the probability of a conformation that has a particular ( x , y ). Structure visualization was performed using the pymol software…”
Section: Methodsmentioning
confidence: 99%
“…Molecular dynamics (MD) simulations have been widely used to investigate the effects of some factors, such as mutations and small molecules, on the monomeric conformations and protofibril/fibril structural stability of Aβ/Tau/α-Synuclein proteins. Recently, computational investigations are emerging to explore the influence of mutations on the structural properties and aggregation dynamics of fragments of heterogeneous nuclear ribonucleoproteins TDP-43 and FUS. ,, For example, Newell et al investigated the impact of a phosphomimetic mutation S375E on a TDP-43 371–376 protofibrillar hexamer and reported that the phosphorylation of S375 disrupted intermolecular interactions and the protofibril structure . Conicella et al explored the influences of G335A/D/N/S and G338A/D/N/S mutations on the conformational ensemble of the TDP43 310–350 monomer using parallel tempering simulations and found that these mutations enhanced the α-helix propensity .…”
Section: Introductionmentioning
confidence: 99%